SOSIALISASI NILAI-NILAI ISLAM OLEH MAJELIS KUBA KEPADA ANGGOTA MASYARAKAT DI DESA MAWAN - Abang Sahidin; Rustiyarso Rustiyarso; Riama Al Hidayah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe problem of this research is how the socialization of Islamic values by the Kuba assembly to community members in Mawan Village, Selimbau District, Kapuas Hulu Regency. The sub-issue is how the pattern of socialization of Islamic values by the Kuba Assembly to members of the community and what values are promoted by the Kuba Assembly. The form of this research was descriptive-qualitative. Data collection techniques are documentation, interview and observation. The results of the research showed that socialization is done by way Jaulah and Khuruj. The socialization in Jaulah were done by way Takrir and coming to the house of the community. Socialization in Khuruj were done by way of Bayan, Ta'lim, Mudzakarah and Jaulah. The Islamic values socialized by the Kuba Assembly are eating and dressing, such as eating in congregation, eating on a sufrah, using a cap when eating, sitting tawadhu, tasting salt before eating, eating using three fingers. Wear a robe or a jubbah, wear a cap and turban, use a syari veil with a purdah.Keywords: Islamic Values, Kuba Assembly, Socialization